Psychosocial burden during corona: Results of a scoping review on families with children aged 0–5 years Psychosoziale Belastungen während Corona: Ergebnisse eines Scoping Reviews zu Familien mit Kindern zwischen 0 und 5 Jahren - Ghezih, Sarah; Lux, Ulrike; Löchner, Johanna; Chakraverty, Digo; Neumann, Anna; Renner, Ilona; Hager, Tina; Ulrich, Susanne M. (Prävention und Gesundheitsförderung, 2024)
Background: The paper provides an overview of stress and resources as well as the use of support services of families with young children during the coronavirus disease 2019 (COVID-19) pandemic in Germany. Purpose: A scoping review was conducted to identify the impact of the COVID-19 pandemic on parental and child well-being and to examine changes in the use of social and professional support among young families by conducting a scoping review. Results: From a total of 14,776 studies searched by PsycInfo, PubMed, Medline, APA PsycArticles, APA PsycInfo and Google Scholar, 20 studies that met the following criteria were ultimately included: (i) child age between 0 and 5 years, (ii) parents and/or children as target population, (iii) study conducted during the pandemic in Germany, the USA, or the United Kingdom. Study evidence suggests that the psychosocial health of families with children aged 0–5 years deteriorated during the COVID-19 pandemic. The loss of social and professional support during the pandemic is significant in this regard. Conclusion: Families in psychosocial stress situations can benefit particularly from support. This is relevant for support programs for young families, such as early childhood intervention and other services in future crises.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Child health; Crisis research; Early intervention; Family health; Social support